The Association Between Diabetes and Dementia Among Elderly Individuals: A Nationwide Inpatient Sample Analysis. (May 2016) - Sherzai, Dean; Sherzai, Ayesha; Lui, Keith; Pan, Deyu; Chiou, Daniel; Bazargan, Mohsen; Shaheen, Magda
Background/Aim: To date, few studies have cross-examined the relationship between diabetes mellitus (DM) and dementia nationally. There is also a lack of evidence regarding dementia subtypes and how this relationship changes among older individuals. The objective was to better delineate this relationship and influence of multiple comorbidities using a nationwide sample. Methods: Data were obtained from the Nationwide Inpatient Sample 1998 to 2011 using appropriate International Classification of Diseases, Ninth Version codes. Descriptive and bivariate analysis was performed. Multivariate nominal logistic regression models adjusted for age, sex, race, and comorbidities explored the independent relationship between Alzheimer dementia (AD), non-Alzheimer dementia (VaD), and diabetes. Results: 21% of the participants were diabetic patients, 3.7% had AD, and 2.2% had VaD. Diabetes prevalence in AD, VaD, and no dementia groups were 20.6%, 24.3%, and 26.2%, respectively. In the unadjusted model, those with DM had lower odds of AD (odds ratio [OR] 0.73; 95% confidence interval [CI] 0.72-0.74) and VaD (OR 0.91, 95% CI 0.89-0.92). Adjusting for age, sex, race, and comorbidities, diabetic patients had significantly higher odds of VaD (OR = 1.10, 95% CI 1.08-1.11) and lower odds of AD (OR 0.87, 95% CI 0.86-0.88). Inclusion of interaction terms (age, race/ethnicity, depression, stroke, and hypertension) made the relationship between diabetes and VaD not significant (OR 1.002, 95% CI 0.97-1.03), but the relationship of DM with AD remained significant (OR 0.57, 95% CI 0.56-0.58; P < .05). Conclusion: Patients with a diagnosis of diabetes mellitus had lower odds of having AD. Age, race/ethnicity, depression, stroke, and hypertension modified the relationship between DM and both VaD and AD. Further exploration of the relationship between DM and AD is warranted.